1976
DOI: 10.1073/pnas.73.12.4516
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 3T3 fibroblasts into adipose cells: triggering of differentiation by prostaglandin F2alpha and 1-methyl-3-isobutyl xanthine.

Abstract: Green and Kehinde [( ) Cell 1, 113-1161 have isolated clones of Swiss 3T3 fibroblasts that are able to convert to adipose cells. In this paper we report on two chemicals (prostaglandin F2a, 0.1 ug/ml, and 1-methyl-3-isobutyl xanthine, 0.5 mM) that are able to rapidly and irreversibly program the fibroblasts to differentiate into adipose cells. Confluent cultures treated with prostaglandin F2a and insulin for 3-5 days, followed by insulin alone for 7-48 hr, yield numerous adipocyte colonies compared to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(75 citation statements)
references
References 11 publications
4
70
1
Order By: Relevance
“…In human obesity, when body weight exceeds 170% of ideal, a maximum adipocyte size of the twice normal is achieved and hyperplasia becomes increasingly manifest with greater severity [12]. It is well known that insulin stimulates proliferation and dif- ferentiation of preadipocytes [13,14]. The possible asymmetric cell division of mature human adipocytes has also been reported [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In human obesity, when body weight exceeds 170% of ideal, a maximum adipocyte size of the twice normal is achieved and hyperplasia becomes increasingly manifest with greater severity [12]. It is well known that insulin stimulates proliferation and dif- ferentiation of preadipocytes [13,14]. The possible asymmetric cell division of mature human adipocytes has also been reported [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been reported about the acceleration of differentiation using cell lines or stromal vascular cells, stimulated by insulin [10], growth hormone [15], indomethacin [25] and prostaglandin [21]. On the other hand, the influence of ECM on the differentiation of fat cells, especially with respect to promoting effects, has scarcely been described.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were exposed to a standard protocol for adipocyte induction from preadipocytes which involves an initial treatment with an 'adipocyte differentiation medium' containing serum (Green and Meuth, 1974), insulin (Green and Kehinde, 1975), dexamethasone (Rubin et al, 1978;Student et al, 1980), 1-methyl-3-isobutylxanthine (a cAMP-phosphodiesterase inhibitor, also known as IBMX) (Russell and Ho, 1976) and PPARc agonists (De Coppi et al, 2006) for 3 days (Hauner et al, 1989;Tang and Lane, 2012). This was followed by an 'adipocyte nutrition medium' with only a small amount of serum (2%) and insulin for 7 or 15 days (Tchkonia et al, 2006).…”
Section: Adipogenic Induction Mediummentioning
confidence: 99%